Mellom kulturens bokstav og kulturens ånd - Ødemark, John (Tidsskrift for kulturforskning, 2003)
This paper examines how certain aspects of modern cultural and anthropological thought is prefigured in Spanish missionary ethnography from the 16th Century. The Stage for this examination is set by an analysis of the critique of anthropology performed by Vassos Argyrou in Anthropology and the will to meaning. A postcolonial Critique (2002). Here Argyrou claims that modern anthropological consciousness still relates to "the other" in ways that are prefigured by Spanish missionaries and theologians in the 16th Century. I test this narrative of continuity by analysing how Bartolomé de Las Casas and Bernardino de SahagÃƒÂºn describe the human sacrifice among the Aztecs in New Spain [Mexico]. By focusing on these early ethnographers I am able to sketch a model of a fundamental difference between to pre-cultural and pre-modern discourses on heathen culture; one based on natural theology and another based on demonology.